Teaching in today's inclusive classrooms : - Gargiulo, Richard M. (Wadsworth Cengage Learning, 2013)
Gargiulo/Metcalf is intended for the Inclusion or Mainstreaming course offered in schools and colleges of education. The course is typically required of all pre-service, general education teachers; some schools may require pre-service special educators take this course in addition to or instead of the typical Introduction to Special Education. The course is taken during the sophomore or junior year; graduate programs may also offer this course.